2022
DOI: 10.3390/s22197321
|View full text |Cite
|
Sign up to set email alerts
|

Research on Emotion Recognition Method Based on Adaptive Window and Fine-Grained Features in MOOC Learning

Abstract: In MOOC learning, learners’ emotions have an important impact on the learning effect. In order to solve the problem that learners’ emotions are not obvious in the learning process, we propose a method to identify learner emotion by combining eye movement features and scene features. This method uses an adaptive window to partition samples and enhances sample features through fine-grained feature extraction. Using an adaptive window to partition samples can make the eye movement information in the sample more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Currently, MOOCs are mainly applied in general education courses, but their effects are not ideal in some professional courses, such as technology and art (VOA, 2012). For example, Shen et al (2022) pointed out that face-to-face interaction was lost in online education, and therefore, teachers could not provide feedback on students' emotions during the learning process (Shen et al, 2022). Tormanen et al (2022) found that students' learning enthusiasm and emotional fluctuations were low because of a lack of collaborative learning between classmates in online learning (Tormanen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, MOOCs are mainly applied in general education courses, but their effects are not ideal in some professional courses, such as technology and art (VOA, 2012). For example, Shen et al (2022) pointed out that face-to-face interaction was lost in online education, and therefore, teachers could not provide feedback on students' emotions during the learning process (Shen et al, 2022). Tormanen et al (2022) found that students' learning enthusiasm and emotional fluctuations were low because of a lack of collaborative learning between classmates in online learning (Tormanen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shen et al. (2022) pointed out that face-to-face interaction was lost in online education, and therefore, teachers could not provide feedback on students' emotions during the learning process (Shen et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation